2009
DOI: 10.1142/s0192415x09007430
|View full text |Cite
|
Sign up to set email alerts
|

The Anti-Hyperglycemic Effect of Plants in Genus Gynura Cass.

Abstract: Gynura divaricata (L.) DC and G. bicolor DC are used as secret recipes to treat diabetes mellitus in some parts of China. Pharmacological tests were performed to prove the anti-hyperglycemic effect of these two plants of genus Gynura Cass. in this study. Both water and 95% ethanol extracts of fresh G. divaricata had significant effects on lowering blood glucose level in normal mice, in which the dose of 0.4 g (crude drug)/kg of 95% ethanol extract was more effective than 50 mg/kg glyburide. The ethyl acetate a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(21 citation statements)
references
References 1 publication
0
21
0
Order By: Relevance
“…Many Gynura species have recently been shown to exhibit hypoglycemic and carbohydrate enzyme inhibitory activities [1114]. The inhibition of yeast α-glucosidase activity of the extracts and pure phenolic compounds 1 – 7 were determined.…”
Section: Resultsmentioning
confidence: 99%
“…Many Gynura species have recently been shown to exhibit hypoglycemic and carbohydrate enzyme inhibitory activities [1114]. The inhibition of yeast α-glucosidase activity of the extracts and pure phenolic compounds 1 – 7 were determined.…”
Section: Resultsmentioning
confidence: 99%
“…Scientific studies on the use of locally grown G. bicolor to ensure its efficacy and nontoxicity have not been carried out. Several phytochemical and biological reports showed that G. bicolor cultivated in Japan, China, and Taiwan has antihyperglycemic effect [2, 4], anti-inflammation activity [5], and antioxidant capacity [6] and could induce apoptosis in HL60 leukemia cells [7]. Chemical constituents such as flavonols, anthocyanins, sesquiterpenes, terpenes, and megastigmane-type norisoprenoids had also been isolated from G. bicolor leaves [3, 810].…”
Section: Introductionmentioning
confidence: 99%
“…The pooled analyses indicated that Tangminling pill was more efficacious in decreasing glucose level, body weight, and improving β-cell function, with no more drug-related adverse events, than placebo treatment in T2DM patients. Traditional Chinese medications, mainly edible herbs, have been widely used in clinical practice in China for more than 2000 years [16][17][18] (Table 3). Three bioactive alkaloids have been isolated from Rhizoma coptidis, including berberine, coptisine, and jatrorrhizine.…”
Section: Discussionmentioning
confidence: 99%